Knowledge, attitudes, and anxiety levels of parents with suspected COVID-19 children: A cross-sectional study in Turkey - Konukbay, Dilek; Kapan, Emine; Yildiz, Dilek; Unay, Bulent (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the knowledge, attitudes and anxiety levels of parents with children suspected of having coronavirus disease-2019. Method: The descriptive, cross-sectional study was conducted at the coronavirus disease-2019 outpatient clinic of a tertiary hospital in Ankara, Turkey, between January and August 2021, and comprised parents who presented with suspicions of coronavirus disease-2019 in their children. Data was collected using a questionnaire to assess the parents' knowledge and attitudes towards coronavirus disease-2019, the State-Trait Anxiety Inventory-I and the visual analogue scale to determine levels of fear related to coronavirus disease-2019. Data was analysed using SPSS 25. Results: Of the 307 subjects with mean age 40.53±8 years (range: 22-68 years), 237(77.2%) were mothers, 125(40.7%) were high school graduates and 130(42.3%) were employed. The mean score for fear of infection in the children was 7.95±2.64 (range: 0-10, while the mean score for fear of infection of self and other family members was 7.79±2.63 (range: 0-10). The mean scores for knowledge and attitude towards coronavirus disease-2019 were 24.93±4.05 (range: 6-30) and 64.86±26.53 (range: 18-90), respectively. The mean anxiety score was 39.74±7.27 (range: 20-80). There was a significant relationship of knowledge and attitude towards coronavirus disease-2019 with the mother-father status, age and education levels of the participants (p<0.05). There was also a significant relationship of anxiety with the mother-father status and employment status of the parents (p<0.05). Conclusion: Parents had a high level of knowledge about coronavirus disease-2019, a positive attitude towards protective measures, and a moderate level of anxiety. They had a high level of fear of transmitting the disease to themselves, their children and other family members. Key Words: COVID-19, Attitude, Knowledge, Anxiety.